DIABETES MELLITUS A RISK FACTOR OF GASTRIC CANCER : SYSTEMATIC REVIEW - Azwar Aziz, Mohamad; Intan Kania, Yulia; Aziz, Ilham; Sibli, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: It is estimated that 500 million individuals globally would have diabetes mellitus (DM) by 2030. A deadly tumor that affects the digestive tract is called gastric cancer (GC). It ranks as the fourth leading cause of cancer death worldwide and the fifth most common kind of cancer. Every year, there are around 700,000 fatalities and one million new cases of GC globally.Aims : This systematic review is to review the association of diabetes mellitus as a risk factor of gastric cancer.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 343 articles, whereas the results of our search on SAGEPUB brought up 2178 articles, our search on SCIENCE DIRECT brought up 23102 articles. The results of the search conducted for the last year of 2014 yielded a total 231 articles for PubMed, 1017 articles for SAGEPUB and 12260 articles for SCIENCE DIRECT. In the end, we compiled a total of  5 papers, 2 of which came from PubMed, 1 of which came from SAGEPUB and 2 of which came from SCIENCE DIRECT. We included five research that met the criteria.Conclusion: In summary, there is no direct association of diabetes mellitus and gastric cancer, but diabetes mellitus can increase the risk factor of gastric cancer cases.